Assessment of the Understanding of Ergonomics Role in Triggering Musculoskeletal Pain Amongst Dentists of Karachi, Pakistan - Asra Afzal, Shaista Zafar, Faiqa Ashfaq, Javaria Javaid, Ramsha Taj, Hassan Mehdi (Pakistan Journal of Medical & Health Sciences, 2023)
Obective: The purpose of the study is to assess the understanding of ergonomics role in triggering musculoskeletal pain amongst dental professionals in Pakistan. Methodology:A cross-sectional survey was carried out in hospitals and private clinics in Karachi. A total of 230 dentists were recruited in the study, 121 were males and 109 were females. Dentists aged between 27 years to 60 years with a clinical experience of minimum 5 years and no hereditary musculoskeletal disorder were included in the study. The questionnaire was divided into three segments recording; practice details, understanding of the work-related MSD and attitude towards WMSD. The collected data were computed and analyzed in SPSS.21.0. Results:According to the study 169 (73.5%)dentists claimed to have to experienced musculoskeletal disorder pain. Lower back [4.77± 2.31] and neck[4.74± 2.23] followed by shoulder pain[ 4.93± 2.46]were the most common complaints. With respect to pain in different parts, female practitioners consistently reported more pain in every zone compared to males, irrespective of age. However, back pain reported the highest frequency with increasing BMI and decreased with age. Conclusion: The study showed a significant association of musculoskeletal pain with torsion/cervical flexion of the neck, employing for better approach during the procedures; however, with an increase in clinical experience the pain site changed from the lower back to wrist and hand, with respect to gender. Keywords: Dental rofesionals, Ergonomics, Lower back pain, Musculoskeletal pain.